Dual-beam laser autofocusing system based on liquid lens. (February 2017) - Zhang, Fumin; Yao, Yannan; Qu, Xinghua; Zhang, Tong; Pei, Bing
Abstract: A dual-beam laser autofocusing system is designed in this paper. The autofocusing system is based on a liquid lens with less moving parts and fast response time, which makes the system simple, reliable, compact and fast. A novel scheme "Time-sharing focus, fast conversion" is innovatively proposed. The scheme effectively solves the problem that the guiding laser and the working laser cannot focus at the same target point because of the existence of chromatic aberration. This scheme not only makes both guiding laser and working laser achieve optimal focusing in guiding stage and working stage respectively, but also greatly reduces the system complexity and simplifies the focusing process as well as makes autofocusing time of the working laser reduce to about 10 ms. In the distance range of 1 m to 30 m, the autofocusing spot size is kept under 4.3 mm at 30 m and just 0.18 mm at 1 m. The spot size is much less influenced by the target distance compared with the collimated laser with a micro divergence angle for its self-adaptivity. The dual-beam laser autofocusing system based on liquid lens is fully automatic, compact and efficient. It is fully meet the need of dynamicity and adaptivity and it will play an important role in a number of long-range control applications. Highlights: A dual-beam laser autofocusing system for long-range laser application is designed. A newest technology — electrically tunable liquid lens for autofocusing is used. "Time-sharing focus, fast conversion" scheme for fast focus is proposed. The autofocusing system is fully meet the need of dynamicity and adaptivity.